The study on the relationship between work-life balance towards staff retention at Perbadanan Memajukan Iktisad Negeri Terengganu (PMINT) / Nurul Akma Hamazah - Hamazah, Nurul Akma (Faculty of Business and Management, 2018)
This research involves discovering to study the relationship between work-life balances towards staff retention at Perbadanan Memajukan Iktisad Negeri Terengganu (PMINT). The element of work-life balance includes Flexible Work Schedule, Work-Family Conflict, Family-Work Conflict, Job Sharing and Job Burnout. Almost 140 set of questionnaires has been distributed in order to obtain a data and the total of the returned questionnaire was 117 set. This study uses the Statistical Package for Social Science (SPSS) version 21.0 to analyze the result. The descriptive analysis and Pearson correlation analysis has been used in order to reply to the research question. All the result reveals that each of the elements has a positive and negative relationship to the retention of the staff.